Experimental Study based on the Implementation of a Regulatory Framework for the Improvement of Cyber Resilience in SMEs - Rodriguez-Baca, Liset S. (2023)
Currently, applying regulations oriented to cybersecurity, cyber resilience is relevant to face the high rates of cyberattacks, which have caused an interruption in the operational processes of organizations, generating an economic loss, and affecting the continuity of their business processes on the web. In this scenario, small and medium-sized enterprises (SMEs) are the most affected due to their weak technological infrastructure. Given this, this experimental study was developed to implement a regulatory framework for the improvement of cyber resilience; the criteria anticipate, resist, recover and evolve presented significant statistical values of improvement after the application of the experiment. This research contributes to counteract the refusal to use information technologies for business development; Improvement actions were carried out to face threats and computer vulnerabilities to which organizations are exposed when carrying out operations in cyberspace.